Pengaruh Rekrutmen Dan Pelatihan Terhadap Kinerja Karyawan Melalui Komitmen Organisasi Studi Kasus Pada PT. Perkebunan Nusantara 7 (PTPN.7) Di Bekri - Suwarto, Suwarto; Sugeng, Sugeng; Oktavia, Nurbaiti (Jurnal Manajemen DIVERSIFIKASI, 2023)
The purpose of this study was to determine the effect of recruitment on employeeperformance, the effect of training on employee performance, the effect of recruitment onperformance through organizational commitment, the effect of job training on performancethrough organizational commitment, and the effect of recruitment, training, andorganizational commitment on employee performance. The research method usesquantitative research that measures the variables of recruitment, training, and employeeperformance and organizational commitment. The population in this study were employeesof PTPN VII Bekri with a total sample of 60. The instrument in this study used aquestionnaire. Data analysis in this study used path analysis regression test. The resultsshowed that Employee Recruitment had a positive and significant effect on employeeperformance at PTPN VII in Bekri. Job training has a positive and significant effect onemployee performance at PTPN VII in Bekri. Employee recruitment and job training have apositive and significant impact on employee performance at PTPN VII in Bekri. There is aneffect of recruitment on employee performance through organizational commitment toemployees at PTPN VII in Bekri. There is an effect of training on emp